UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR PPKn MELALUI MODEL DISCOVERY LEARNING DI SMAN 1 BUNGO - sumirna, sumirna (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This research is a class action research / CAR (Classroom Action Research) which aims to improve Civics learning outcomes through discovery learning models for students of class X IPS 3 SMAN 1 Bungo. This research was conducted at SMAN 1 Bungo, with the subjects being students of class X IPS 3 in the even semester of the 2019/2020 school year. The data in this study are observational data about student activities and student learning outcomes data. From the results of observations, student activity has increased every cycle. Cycle I obtained a value of 58 with good criteria, cycle II obtained an activity value of 66.07 with good criteria. Cycle III obtained a value of 76.19 with very good criteria, so that there was an increase in student learning activities from cycle II to cycle III, which was 10.12. Based on the learning outcomes data, the average value in the first cycle was 71.79. Cycle II was 73.13 and in cycle III was 79.11, thus there was an increase from cycle I to cycle II of 1.34 and from cycle II to cycle III of 5.98. Based on the completeness data, in the first cycle, only 28.6% have been completed. In the second cycle as much as 25% were declared to have been completed. In the third cycle, 82.14% were declared to have been completed. So it can be concluded that learning with discovery learning models can increase student activity and learning outcomes.